Yäkän yeza iqtisad učur tori (2012)
Das war eine offizielle Webseite der Verwaltungsbehörde für die Landwirtschaft der Kreisregierung Yäkän (Yarkant) des Bezirks Kaschgar der Region Xinjiang. Diese Webseite wurde seit Ende 2012 nicht aktualisiert. Auf dieser Webseite finden sich Beiträge über die Landwirtschaft im Kreis Yäkän, die Landwirtschaftspolitik und unterschiedliche Gesetze der Volksrepublik China, regionale Verordnungen der Autonomiebehörde des Uigurischen Autonomen Gebietes Xinjiang, die Parteidisziplin der Chinesischen Kommunistischen Partei. - This was an official website of the Administrative Department of Agriculture of Yäkän (Yarkant) County Government of Kashgar District of Xinjiang Region. This website has not been updated since the end of 2012. On this website, there are articles about agriculture in Yäkän County, agricultural policies and different laws of the People's Republic of China, regional regulations of the Autonomous Administration of Xinjiang Uyghur Autonomous Region, party discipline of the Chinese Communist Party.